Factors Influencing Evidence-Based Practice Implementation Among Nurses in Psychiatric–Mental Health Hospitals. - Gang, Moonhee; Ahn, Yujin; Gwak, Donghyeon (Journal of Psychosocial Nursing & Mental Health Services, 2026)
Purpose: Although evidence-based practice is essential for improving care quality, its use in psychiatric–mental health nursing remains limited. The current study aimed to identify key factors influencing the implementation of evidence-based practice among nurses working in mental health hospitals. Method: A descriptive, cross-sectional design was used. Participants were 200 psychiatric–mental health nurses working in eight regional mental health hospitals in South Korea. Data were collected through validated self-report instruments, including the Evidence-Based Practice Questionnaire, Critical Thinking Disposition Scale, Organizational Culture and Readiness Scale, and Attitudes Toward Mental Illness Scale. Analyses included descriptive statistics, t tests, analysis of variance, Pearson's correlations, and multiple regression. Results: Critical thinking (β = 0.41, p < 0.001), attitudes toward mental illness (β = 0.17, p = 0.004), organizational culture and readiness (β = 0.12, p = 0.04), and research activity experience (β = 0.12, p = 0.039) significantly predicted evidence-based practice implementation, explaining 36.9% of the variance (F = 17.64, p < 0.001). Conclusion: Findings indicate that critical thinking, research experience, organizational culture, and attitudes toward mental illness predict evidence-based practice in psychiatric–mental health nursing.